A study on the factors that influence performance of sales in “Pertubuhan Peladang Kawasan Kuala Terengganu (PPK KT)” / Ahmad Fikri Al-Amin Mohd - Mohd, Ahmad Fikri Al-Amin (2013)
“Pertubuhan Peladang Kawasan Kuala Terengganu (PPK KT)” is one of the organization that help farmers in farming products and advice about farming. Each customers come purchase in organization can make the increasing sales in the organization. In recent year, the performance sales in “Pertubuhan Peladang Kawasan Kuala Terengganu (PPK KT)” not achieve their target and it makes problems for their organization. Their organization get profits but the profits very small and not stable which is decrease and increase from years to years. PPK Kuala Terengganu also has their competitors and it make they must compete each other’s to attract more customers to increase their profits. That situation has made the researcher want to study how to improve performance of sales in PPK Kuala Terengganu. The researcher come out with four variables which are variety of products, services provided, quality of products and prices of products in order to study the factors that influence performance of sales in “Pertubuhan Peladang Kawasan Kuala Terengganu (PPK KT)”. The researcher distributed the questionnaire to 150 respondents in order to know what the factors that influence performance of sales. From the finding analysis it can be conclude that the significant factors that influence performance of sales in “Pertubuhan Peladang Kawasan Kuala Terengganu ( PPK KT )” is services provided and their price of products. “Pertubuhan Peladang Kawasan Kuala Terengganu (PPK KT)” also can make the improvement to ensure their sales will be increase from years to years and this can make their organization become stable in markets and make their competitors cannot compete with them.